2019
DOI: 10.4149/bll_2019_068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of N-acetylcysteine on cisplatin induced cardiotoxicity

Abstract: OBJECTIVES: Recent studies reported that oxidative stress is an important mechanism that contributes to cisplatin induced cardiotoxicity. In the present study, the effects of N-acetylcysteine (NAC), which is an antioxidant, on cisplatin induced cardiotoxicity were investigated in a rat model. METHODS: Thirty two rats were separated into 4 equal groups: Control, NAC-250, CP (cisplatin), CP+NAC. Rats in the experimental groups were treated with a single dose of cisplatin intraperitoneally (ip) (10 mg/kg) and NAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…CDDP increases the total oxidant capacity in tissues. 31,32 One weakness of our study was that we could not perform electrocardiography or echocardiography in mice because of the unavailability of equipment. Another disadvantage might be that we did not use an ALCAR monotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…CDDP increases the total oxidant capacity in tissues. 31,32 One weakness of our study was that we could not perform electrocardiography or echocardiography in mice because of the unavailability of equipment. Another disadvantage might be that we did not use an ALCAR monotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…CP has serious cardiotoxicity and other side effects. [27][28][29] As a result, many tumour patients have to stop taking CP early, and the desired therapeutic effect is not achieved. Therefore, new therapeutic agents with better cardiac protection and safety to attenuate CP-induced cardiotoxicity are required.…”
Section: Discussionmentioning
confidence: 99%
“…There are some other therapeutic agents which have documented cardioprotective effects on cisplatin induced cardiotoxicity such as N-acetyl cysteine, taurine, coenzyme Q, trimetazidine and rutin 13-17-18-25 . Gunturk et al 25 investigated the effects of Nacetylcysteine (NAC), which is an antioxidant, on cisplatin induced cardiotoxicity in a rat model and they showed that in the CP+NAC group, interstitial edemaand vacuolization was at a significantly lower level than seen in the cisplatin group and hemorrhage was improved in the CP+NAC group compared to the cisplatin only group, but was still high. While in the present study, edema was also more severe in the CP group than the ATRA + CP group but there was a statistically significant difference in the severity of hemorrhage between the ATRA group and the CP and the ATRA + CP groups.…”
Section: Discussionmentioning
confidence: 99%